Immune-Related Gene Expression in Ducks Infected With Waterfowl-Origin H5N6 Highly Pathogenic Avian Influenza Viruses - Wu, Siyu; Zhang, Junsheng; Huang, Jianni; Li, Weiqiang; Liu, Zhiting; He, Zhuoliang; Chen, Zuxian; He, Wanting; Zhao, Bingbing; Qin, Zhifeng; Jiao, Peirong; Liao, Ming (Frontiers in Microbiology, 2019)
Clade 2.3.4.4 H5 avian influenza viruses (AIVs) are widely prevalent and of significant concern to the poultry industry and public health in China. Nowadays, the clade 2.3.4.4 H5N6 virus has become a dominant AIV subtype among domestic ducks in southern China. We found that waterfowl-origin clade 2.3.4.4 H5N6 viruses (A/goose/Guangdong/16568/2016, GS16568 and A/duck/Guangdong/16873/2016, DK16873) isolated from southern China in 2016 could replicate in multiple organs of inoculated ducks. DK16873 virus caused mild infections and killed 2/5 of inoculated ducks, and GS16568 virus did not kill inoculated ducks. Also, the two viruses could be transmitted via direct contact between ducks. DK16873 and GS16568 viruses killed 2/5 and 1/5 of contact ducks, respectively. Furthermore, ducks inoculated with the two H5N6 viruses exhibited different expressions of immune-related genes in their lungs. The expression of RIG-I, TLR3 and IL6 was significantly upregulated at 12 hours post-inoculation（HPI）and most of the tested immune-related genes were significantly upregulated at 3 days post-inoculation(DPI). Notably, the expression of RIG-I and IL-6 in response to DK16873 virus was significantly higher than for GS16568 virus at 12 HPI and 3 DPI. Our research have provided helpful information about the pathogenicity, transmission and immune-related genes expression in ducks infected with new H5N6 AIVs.